Mechanisms of Chromium and Uranium Toxicity in Pseudomonas stutzeri RCH2 Grown under Anaerobic Nitrate-Reducing Conditions - Thorgersen, Michael P.; Lancaster, W. Andrew; Ge, Xiaoxuan; Zane, Grant M.; Wetmore, Kelly M.; Vaccaro, Brian J.; Poole, Farris L.; Younkin, Adam D.; Deutschbauer, Adam M.; Arkin, Adam P.; Wall, Judy D.; Adams, Michael W. W. (Frontiers in Microbiology, 2017)
Chromium and uranium are highly toxic metals that contaminate many natural environments. We investigated their mechanisms of toxicity under anaerobic conditions using nitrate-reducing Pseudomonas stutzeri RCH2, which was originally isolated from a chromium-contaminated aquifer. A random barcode transposon site sequencing library of RCH2 was grown in the presence of the chromate oxyanion (Cr[VI]O42-) or uranyl oxycation (U[VI]O22+). Strains lacking genes required for a functional nitrate reductase had decreased fitness as both metals interacted with heme-containing enzymes required for the later steps in the denitrification pathway after nitrate is reduced to nitrite. Cr[VI]-resistance also required genes in the homologous recombination and nucleotide excision DNA repair pathways, showing that DNA is a target of Cr[VI] even under anaerobic conditions. The reduced thiol pool was also identified as a target of Cr[VI] toxicity and psest_2088, a gene of previously unknown function, was shown to have a role in the reduction of sulfite to sulfide. U[VI] resistance mechanisms involved exopolysaccharide synthesis and the universal stress protein UspA. As the first genome-wide fitness analysis of Cr[VI] and U[VI] toxicity under anaerobic conditions, this study provides new insight into the impact of Cr[VI] and U[VI] on an environmental isolate from a chromium contaminated site, as well as into the role of a ubiquitous protein, Psest_2088.